ORGANIZATIONAL JUSTICE AND ITS ROLE IN ACHIEVING JOB EMBEDDEDNESS THROUGH LEADER HUMILITY- AN INVESTIGATION INTO THE VIEWS OF A SAMPLE OF THE ALHAKIM GENERAL HOSPITAL NURSING STAFF - Dr. Mohammed Saleh Mahdi (Scholar Express Journal, 2023)
The current research aims to identify the role of the dimensions of organizational justice (distributive justice, procedural justice, interactive justice) in achieving job embeddedness through the mediating role of the leader's humility variable, by analyzing the direct and indirect correlation and influence relationships between the research variables, for the data obtained by the questionnaire. distributed to a sample of nursing staff at Al-Hakim General Hospital, as (268) questionnaires were distributed, and (252) correct survey forms were obtained, i.e. with a recovery assess of (95%), and they were analyzed by the developed statistical software (SPSS.26), as well as the statistical program ( AMOS.24). Theoretical results showed that there is a knowledge gap to explain the relationship between Organizational Justice (OJ) and job embeddedness (EMJ) in the presence of leader humility in organizations in general and among a number of nursing cadres in Al-Hakim General Hospital in particular, and the applied results showed a positive and significant effect between organizational justice ( OJ) and job embeddedness (EMJ) in the presence of leader humility, and the study recommended emphasizing The elements of justice in an organization through managers' dedication to enhancing employees' sense of justice, which reflects positively on their behavior within the organization, and the need to pay attention to the concept of job embeddedness by the organization because of its effects Positive for the individual, which is reflected in his sense of belonging and his desire to stay through making maximum effort in job performance
Keywords: organizational justice; job embeddedness; leader humility